2022
DOI: 10.1038/s41598-022-08557-7
|View full text |Cite
|
Sign up to set email alerts
|

Early linguistic experience shapes bilingual adults’ hearing for phonemes in both languages

Abstract: English and Mandarin Chinese differ in the voice onset times (VOTs) of /b/ and /p/. Hence the way bilinguals perceive these sounds may show ‘tuning’ to the language-specific acoustic structure of a bilingual’s languages (a discrete model), or a shared representation across languages (a unitary model). We investigated whether an individual’s early childhood exposure influences their model of phoneme perception across languages, in a large sample of early English-Mandarin bilingual adults in Singapore (N = 66). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The measured threshold of the English phoneme perception in 7.6 to 9.1-year-old bilingual children (M = 27ms, SD = 8) is somewhat earlier than one recent report of phoneme perception in 5.5-to-6.5-year-old bilingual children , which reported a threshold for English (M = 33ms, SD = 13), however no previous studies have investigated perception using the same task in Mandarin Chinese speaking children (M = 33ms, SD = 10). The current finding of different thresholds in two languages is consistent with one previous report of adults from the same language context, where Pan et al (2022) reported adult bilinguals' thresholds of phoneme identification task in English (M = 26ms, SD = 5) and in Mandarin (M = 36ms, SD = 7). The measured slope of the English phoneme perception in 7.6-to-9.1-year-old bilingual children (Median = 0.106, Range: 0.021-6.031) is relatively mature compared to the recent report of phoneme perception in 5.5-to-6.5-year-old bilingual children , which reported the slope for English (Median = 0.045, Range: −0.006-0.213).…”
Section: Slopesupporting
confidence: 92%
See 1 more Smart Citation
“…The measured threshold of the English phoneme perception in 7.6 to 9.1-year-old bilingual children (M = 27ms, SD = 8) is somewhat earlier than one recent report of phoneme perception in 5.5-to-6.5-year-old bilingual children , which reported a threshold for English (M = 33ms, SD = 13), however no previous studies have investigated perception using the same task in Mandarin Chinese speaking children (M = 33ms, SD = 10). The current finding of different thresholds in two languages is consistent with one previous report of adults from the same language context, where Pan et al (2022) reported adult bilinguals' thresholds of phoneme identification task in English (M = 26ms, SD = 5) and in Mandarin (M = 36ms, SD = 7). The measured slope of the English phoneme perception in 7.6-to-9.1-year-old bilingual children (Median = 0.106, Range: 0.021-6.031) is relatively mature compared to the recent report of phoneme perception in 5.5-to-6.5-year-old bilingual children , which reported the slope for English (Median = 0.045, Range: −0.006-0.213).…”
Section: Slopesupporting
confidence: 92%
“…One recent report on phoneme perception in early adult bilinguals of English and Mandarin in Singapore has shown that the phonemic processing of stop consonants in bilingual speakers differs across a bilingual speaker's two languages (Pan et al, 2022). Adults' early bilingual balance demonstrates a significant correlation with the comprehensive slope of the identification function, affecting both of their languages together: Bilingual adults with more exposure to English during early childhood had steeper slope values in general, and those with more Mandarin had shallower slope values in general.…”
Section: Introductionmentioning
confidence: 99%
“…This model is better aligned with the idea that language‐specific auditory “tuning” occurs only for those speech sounds that are potentially confusable (e.g., sounds that are acoustically similar and occur in similar contexts) and also perform contrastive functions (e.g., sounds that signal differences in function—such as in the case of discriminating meaning among minimal pairs). This approach is more aligned with contemporary models of phonology, such as the perceptual assimilation model—articulatory organ account (Best & McRoberts, 2003 ), and recent studies showing early bilinguals retain separate models for phonological processing of consonants in their two languages (Kremin, Sander & Byers‐Heinlein, 2022 ; Pan, Ke, & Styles, 2022 ).…”
Section: Discussionmentioning
confidence: 87%
“…Work on speech perception in heritage language speakers has the potential to fall into the trap of the deficit model. As we have described, the standard approach to speech perception in bilinguals was motivated by perceptual narrowing and CP (Caramazza et al, 1973;Werker et al, 1981;Werker and Tees, 1984;Flege, 1987;Flege et al, 1995b;Mayo et al, 1997;Sebastián-Gallés andBosch, 2002, 2009;Bosch and Sebastián-Gallés, 2003;Aoyama et al, 2004;Kuhl et al, 2006;Garcia-Sierra et al, 2011;Stölten et al, 2014;Liu and Kager, 2015;Pan et al, 2022). In this context, any deviation in endpoints was interpreted as noisy encoding, deficiency in categories in their languages, or an unstable state of language use.…”
Section: Categorical Perception In the Context Of Heritage Bilingualismmentioning
confidence: 99%